Hubungan Kepuasan Peserta Pelatihan dengan Tingkat Pembelajaran Peserta Pelatihan Pencegahan dan Pengendalian Infeksi - Vera Oktavia Siregar (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2017)
Evaluation of training is a systematic process to collect, describe, interpret  and present information about the training. Evaluation Prevention and Control of Infection training aimed to analyze the correlation between trainees satisfaction with learning level of trainees. This study was a quantitative analytical research using cross sectional design. The results were analyzed with descriptive statistics, dependent t test and Spearman Correlation Test. Trainees satisfaction to the training of Prevention and Control of Infection obtained good results with the percentage of 74.2%. Learning level of trainees Prevention and Control of Infection had a different average value of pre test and post test so as to increase the knowledge of trainees. Based on the correlation trainees satisfaction with learning level of trainees it can be concluded that the success of every level Kirkpatrick model evaluation is important because there is a level depth evaluation. Keywords: training evaluation, kirkpatrik model, learning level, trainees satisfaction